Produktivitas Dan Keuntungan Usahatani Padi Lokal Varietas Mayang (Oryza sativa L) Di Desa Bunipah Kecamatan Aluh Aluh Kabupaten Banjar - Mahdalena, Zulipah; Bakri, Ahmad (Chlorophyl, 2023)
This research aims to determine the cost, production, revenues, profit and productivity of lokal paddy farming of the Mayang variety in Bunipah village Aluh-aluh district. The method used is a survey method with observation n techniques. The sampling technique used the census method, so that 33 farmer respondens were obtained. The results of this research show that the everage production of lokal rice of the Mayang variety in Bunipah village is 4.297,5 kg /farmers or 4,29 tons/hectare. The everage total cost is Rp.20.722.369,10/farmer. So the average revenue obtained is Rp.42.975.242,42/farmer or Rp.30.052.447,55/hectare. The average profit obtained during one production process is Rp.22.252.873,32/farmer or Rp.15.561.449,87/hectare. Thr everage productivity obtained was 2,93 tons/hectare